#TITLE_ALTERNATIVE# - DWI NURCAHYO NIM 10210084, WAHYU
In general, conventional seismic methods, the source of vibration and signal receiver placed on a surface. However, the method of Vertical Seismic Profiling (VSP), the signal receiver is placed at a certain depth. So the resulting data will be more accurate. This is because the seismic wave energy does not spread as far as surface seismic methods so the energy have less attenuation. This method is taken by putting the signal receiver in the borehole to a depth of 40 m by using 6 different offsets: 5 m, 10 m, 15 m, 20 m, 25 m and 30 m. The data will be processed using software Vista. The results of this method in the form of corridor stack will be compared with surface seismic data. The results of the VSP method shows there is only one layer below the surface, and the results correspond to the results of surface seismic method.